2015
DOI: 10.1016/j.ymgmr.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of oral biotin treatment in patients with biotinidase deficiency — Twenty years follow-up

Abstract: IntroductionBiotinidase deficiency (BTD) is an inborn error of biotin metabolism inherited as an autosomal recessive trait. Due to the, biotinidase deficiency, biotin is not recycled. Individuals with BTD usually exhibit neurological and cutaneous abnormalities unless treated with biotin. Supplementation with biotin may either ameliorate or if early introduced even prevent symptoms when introduced presymptomatically.Patients and methodsSince 1991, 22 Polish patients from 19 families have been diagnosed with BT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This is consistent with Wolf et al's study conducted in the United States of America (USA), whereas one patient was found to have a c.1361A>C (p.Tyr454Cys) mutation with a complete absence of the biotinidase activity (0.0 nmol/min/mL) [22]. The last detected mutation in our cohort was c.235C>T (p.Arg79Cys) in exon 2, which is common in different populations from South China [23], Iran [24], Poland [25], Turkey [17,26,27], United States [22], and Sweden [28]. The Iranian, Turkish, and American children were found to have an enzyme activity of 0.11, 0.13, and 0.0 nmol/min/mL, respectively [22,24,26].…”
Section: Discussionmentioning
confidence: 88%
“…This is consistent with Wolf et al's study conducted in the United States of America (USA), whereas one patient was found to have a c.1361A>C (p.Tyr454Cys) mutation with a complete absence of the biotinidase activity (0.0 nmol/min/mL) [22]. The last detected mutation in our cohort was c.235C>T (p.Arg79Cys) in exon 2, which is common in different populations from South China [23], Iran [24], Poland [25], Turkey [17,26,27], United States [22], and Sweden [28]. The Iranian, Turkish, and American children were found to have an enzyme activity of 0.11, 0.13, and 0.0 nmol/min/mL, respectively [22,24,26].…”
Section: Discussionmentioning
confidence: 88%
“…While biotin treatment is demonstrably effective and safe, there remains some uncertainty regarding the optimal dosage for patients with partial BD. Studies suggest that lower doses, ranging from 5 to 10 milligrams per day, might be su cient for managing partial BD in children [12,38]. Early intervention is critical for achieving positive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, oral biotin supplementation offers a wellestablished and effective therapy for BD. However, certain complications, such as hearing loss, remain irreversible once established [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…There were three out of four patients affected by this L215F mutation, and the patients had symptoms such as hearing loss or vision problems. 59 In Italy, a patient showed a new variant of T492I with a combination of D444H, and the mother didn't have a similar mutation in her genomic DNA, which suggests the mutation is due to a de novo origin of maternal germline mosaicism. 60 The prevalence of BTD deficiency in the European population is estimated at one in 61,000.…”
Section: Mutations In Other Populationsmentioning
confidence: 99%
“…In addition, asymptomatic BTD patients take 5 mg of oral biotin daily. A study of 22 Polish pediatric patients was screened for biotin follow-up for 20 years by Szymanska et al 59 They routinely monitored the patient's urine organic acid (3-hydroxyisovaleric acid) by gas chromatography mass spectrometry. Once a year, ophthalmological, audiological, and neurological evaluations were also conducted.…”
Section: Efficacy Of Biotin Treatmentmentioning
confidence: 99%